Pengaruh Beban Kerja dan Burnout terhadap Kepuasan Kerja pada Pegawai Fakultas Ekonomi dan Bisnis Universitas Negeri Padang - Asma Lidya; Afriyeni Afriyeni (ARZUSIN, 2025)
The main issue addressed in this study is the low level of employee job satisfaction at the Faculty of Economics and Business, Universitas Negeri Padang, which is suspected to be caused by high workload and increased burnout levels. This research aims to examine the effects of workload and burnout on employee job satisfaction. A quantitative approach with a survey technique was employed. Primary data were collected through questionnaires distributed to the entire population of 37 employees using total sampling. Data analysis was conducted using SPSS through validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results indicate that workload (X₁) and burnout (X₂) have a significant negative effect on job satisfaction (Y), meaning that higher workload and burnout levels correspond to lower employee job satisfaction. The study concludes that management plays a crucial role in managing workload and reducing burnout to create a healthier and more supportive work environment. Practical implications include the need for organizational policies that balance workload and prioritize employee well-being to sustainably enhance job satisfaction and productivity.